The Demography, Clinical Characteristics, and White Blood Analysis of Leprosy Reactions in Multibacillary Leprosy: A Retrospective Study - Tanojo, Natalia; Damayanti, Damayanti; Utomo, Budi; Ervianti, Evy; Murtiastutik, Dwi; Cita Rosita Sigit Prakoeswa; Listiawan, M. Yulianto (Faculty of Medicine, Universitas Airlangga, 2021)
Background: Leprosy is a neglected tropical disease caused by chronic granulomatous infection of Mycobacterium leprae. Indonesia ranks third in new case findings, with 84% of the case being multibacillary (MB) leprosy. MB leprosy cases have a higher risk of leprosy reactions and physical disabilities that decrease quality of life. Purpose: To determine the demographic, clinical characteristics, and white blood analysis of newly diagnosed MB leprosy patients, especially concerning leprosy reactions. Methods: This is a descriptive retrospective study with a cross-sectional design that describe the following data: domicile, gender, age, treatment status, disabilities, body mass index (BMI); bacterial index (BI), morphological index (MI), white blood cell (WBC) and differential counts, and thrombocyte count. Result: This study included 176 adult MB cases, predominantly male aged 20–39 years old with average BMI, lived in Surabaya with negative history of multi-drug therapy, disability, BI, nor MI. The grade 2 disability (G2D) percentage in this study setting than in Indonesia (10.7% vs. 6.43%). The WBCs, especially neutrophil count, was higher in T2R group. Monocyte and lymphocyte counts were relatively similar. There was an increase in thrombocyte count in leprosy reaction groups. Conclusion: MB leprosy in the endemic area, which is more commonly found in productive-aged male, displayed higher G2D than global Indonesia population. Thus denotes the importance of active case findings. The difference in blood analysis characteristics between MB leprosy with and without reactions may serve as the foundation for future study.